2020
DOI: 10.1002/smll.202002616
|View full text |Cite
|
Sign up to set email alerts
|

Nanofountain Probe Electroporation Enables Versatile Single‐Cell Intracellular Delivery and Investigation of Postpulse Electropore Dynamics

Abstract: Introducing exogenous molecules into cells with high efficiency and dosage control is a crucial step in basic research as well as clinical applications. Here, the capability of the nanofountain probe electroporation (NFP‐E) system to deliver proteins and plasmids in a variety of continuous and primary cell types with appropriate dosage control is reported. It is shown that the NFP‐E can achieve fine control over the relative expression of two cotransfected plasmids. Finally, the dynamics of electropore closure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…We have shown in a previous study that sufficient contact is made in this process to increase the transmembrane potential beyond the electroporation threshold. [ 47 ] We have also investigated the effect of the extent of contact on delivery efficiency and cell viability. [ 41 ] In the current study, contact is determined when the resistance change (≈300–500 kΩ) exceeds 1% of the baseline (≈30–50 MΩ).…”
Section: Resultsmentioning
confidence: 99%
“…We have shown in a previous study that sufficient contact is made in this process to increase the transmembrane potential beyond the electroporation threshold. [ 47 ] We have also investigated the effect of the extent of contact on delivery efficiency and cell viability. [ 41 ] In the current study, contact is determined when the resistance change (≈300–500 kΩ) exceeds 1% of the baseline (≈30–50 MΩ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 46,47 ] Similarly, the resealing of the membrane is much slower in the present case (30–60 min), than what has been shown in the case of nanofountain probe electroporation (few tens of seconds). [ 48 ] We can possibly attribute these differences to longer electroporation pulses and a higher number of pulses, as it has been shown that both the membrane pore size and the resealing time increases with the number of pulses and pulse duration. [ 49 ] Increase in the local electrical field and increased membrane tension on nanostraws may also be an explanation.…”
Section: Resultsmentioning
confidence: 99%
“…This system has been recently used to deliver proteins and plasmids into cells, also providing precise intracellular sampling of model fluorescent proteins, such as calcein and tdTomato. 89 The authors used BSA-AF488 protein as a model biomolecular system to deliver into single cells, in particular analyzing the effect of the number of voltage pulses (typically around 1 V) in enabling functional membrane opening. Excellent plasmid transfection efficiency in HEK 293FT cells was achieved, outclassing the Lipofectamine based assay.…”
Section: Towards Single-cell Intracellular Deliverymentioning
confidence: 99%